Acute electrical muscle stimulation effects on strength and anaerobic power in soccer players - Sofuoğlu, Cem; Fujita, Rafael Akira; Keskin, Kadir; Kamiş, Okan; Akçay, Neslihan (International Journal of Sports Medicine, 2025)
Anaerobic power and lower limb muscle strength are of great importance in soccer, and various preloading strategies are used to improve these abilities. We investigated the acute effects of electrical muscle stimulation on muscle strength and anaerobic power in soccer players. Nineteen healthy male soccer players (age=21.1±1.6 y, training experience=10.1±3.2 y, height=178.1±4.0 cm, and body mass=8.9±3.7 kg) participated in the study. A placebo effect was created without telling the participants that which current (intensity) was applied. After the current applied to the quadriceps muscles, strength and anaerobic power tests were performed. Perceived exertion assessment was also collected after the performance tests. The 75 Hz current exhibited better performance in dominant (p<0.001 and d=0.75) quadriceps muscle group strength (kg). The 75 Hz current condition peak power had significantly higher values than 15 Hz (p<0.05 and d=0.38) and 104 Hz conditions (p<0.05 and d=0.60). Therefore, the 75 Hz current was the most successful in improving lower extremity strength and anaerobic power performances of soccer players. Future research should examine how to utilize sport-specific abilities related to strength and anaerobic power in soccer players for longer periods at peak.
Keywords: Soccer; Football; Electrical Muscle Stimulation; Strength; Anerobic Power